Kinerja Pegawai Dipengaruhi oleh Komunikasi, Iklim Organisasi dan Motivasi Kerja - Daud Woru; Anita Erari; Maman Rumanta (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to describes the ability of communication, organizational climate, and work motivation on the create of employee performance in the Yapen Selatan District. The research method used is quantitative research using statistical procedures. The research instrument was a questionnaire with a Likert scale. The sample in this study were 52 employees in the Yapen Selatan District. Multiple linear regression test with the help of SPSS 22 software is used to determine the effect of independent variables on the dependent variable. The results showed that the variables of communication and work motivation had a significant positive effect on employee performance. While the organizational climate variable has a significant negative effect on employee performance. Communication, organizational climate, and work motivation together have an effect on the performance of South Yapen District employees. Keywords: Communication, Organizational Climate, Work Motivation, Employee Performance.